If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(x + 1) + -4v = 3(2v + 3) + -11 Reorder the terms: 10(1 + x) + -4v = 3(2v + 3) + -11 (1 * 10 + x * 10) + -4v = 3(2v + 3) + -11 (10 + 10x) + -4v = 3(2v + 3) + -11 Reorder the terms: 10 + -4v + 10x = 3(2v + 3) + -11 Reorder the terms: 10 + -4v + 10x = 3(3 + 2v) + -11 10 + -4v + 10x = (3 * 3 + 2v * 3) + -11 10 + -4v + 10x = (9 + 6v) + -11 Reorder the terms: 10 + -4v + 10x = 9 + -11 + 6v Combine like terms: 9 + -11 = -2 10 + -4v + 10x = -2 + 6v Solving 10 + -4v + 10x = -2 + 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. 10 + -4v + -6v + 10x = -2 + 6v + -6v Combine like terms: -4v + -6v = -10v 10 + -10v + 10x = -2 + 6v + -6v Combine like terms: 6v + -6v = 0 10 + -10v + 10x = -2 + 0 10 + -10v + 10x = -2 Add '-10' to each side of the equation. 10 + -10v + -10 + 10x = -2 + -10 Reorder the terms: 10 + -10 + -10v + 10x = -2 + -10 Combine like terms: 10 + -10 = 0 0 + -10v + 10x = -2 + -10 -10v + 10x = -2 + -10 Combine like terms: -2 + -10 = -12 -10v + 10x = -12 Add '-10x' to each side of the equation. -10v + 10x + -10x = -12 + -10x Combine like terms: 10x + -10x = 0 -10v + 0 = -12 + -10x -10v = -12 + -10x Divide each side by '-10'. v = 1.2 + x Simplifying v = 1.2 + x
| 3n-4=2n | | 1.1x-1.62=-1.4 | | 3x+7=7-(4x-9) | | 5.75+5-k= | | x=t^2+3t | | 800x=100x^2 | | 2(5x+3)=98+3x | | 9(8z+9)+6=-273 | | -6(x-7)-7=-7x+2 | | -2.5--0.7=x | | 1.1x=3y-0.4 | | 3p+3.7=9.1 | | -13=x+72 | | n-5=-13 | | .2(x+3)-.5(x+3)=-0.3-0.9 | | 496=62x | | 3/8c=6 | | (n-7)-2n=12 | | 10-2(x+10)=60 | | 7x-1=23+7x | | x+4.07=6.46 | | 6x+6=11-2x | | 8x-15=155 | | -b+8=-15 | | 7s=-49 | | R+(R-12)=90 | | 5x-15=155 | | 7(7x+4)=77 | | 26x-11=5(5x+3)-4 | | 0.2(p+6)-0.7(p+2)=-3 | | 9=3k-4-7k | | 3v=-9 |